1991
DOI: 10.1007/bf01463570
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal papillomatosis with human papillomavirus DNA contracted by a laser surgeon

Abstract: A 44-year-old laser surgeon presented with laryngeal papillomatosis. In situ DNA hybridization of tissue from these tumors revealed human papillomavirus DNA types 6 and 11. Past history revealed that the surgeon had given laser therapy to patients with anogenital condylomas, which are known to harbor the same viral types. These findings suggest that the papillomas in our patient may have been caused by inhaled virus particles present in the laser plume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(124 citation statements)
references
References 21 publications
2
116
0
2
Order By: Relevance
“…This case involved a surgeon who contracted laryngeal papillomatosis after treating anogenital condyloma with a laser. Human papillomvirus (HPV) types 6 and 11, the same types seen in anogenital papillomatosis, were found on this individual's larynx, and there was no other possible way his larynx could have come into contact with the virus [44]. The rarity of documented cases illustrates the difficulty in showing outcome effects.…”
Section: Transmission Of Infectionmentioning
confidence: 96%
“…This case involved a surgeon who contracted laryngeal papillomatosis after treating anogenital condyloma with a laser. Human papillomvirus (HPV) types 6 and 11, the same types seen in anogenital papillomatosis, were found on this individual's larynx, and there was no other possible way his larynx could have come into contact with the virus [44]. The rarity of documented cases illustrates the difficulty in showing outcome effects.…”
Section: Transmission Of Infectionmentioning
confidence: 96%
“…Fortunately, most HPV lesions, particularly those of genital origin, contain fewer particles than those studied in the bovine fibropapilloma model, 41 and the direct inoculation of the laser plume in our study onto the animals may not equal routine clinical exposure. However, there is already a report 42 of a surgeon, who treats anogenital condylomas with the Nd: YAG laser, developing laryngeal papillomatosis containing HPV DNA types 6 and 11.…”
Section: 1mentioning
confidence: 99%
“…The authors found that through inoculation, these animals developed tumors that were proven biochemically and histologically to be infected with the same virus type as was present in the laser plume. Although direct inoculation with bovine papillomavirus laser plume may not compare with clinical exposure during procedures, a review of the literature identified two reports of health care providers developing laryngeal papillomatosis as a result of laser and electrodessication of HPV-related anogenital condyloma with CO 2 and neodymium:yttrium-aluminumgarnet lasers 28,29 in addition to the earlier study by Gloster and Roenigk 5 discussed above.…”
Section: Infectionmentioning
confidence: 94%